Identity in escrow: a case study of a professional golf management university program - Armstrong, C. G. (International Journal of Golf Science, 2023)
In this article, a case study focused on a group of individuals moving through a University-based program accredited by the Professional Golfers Association (PGA) of America is developed. Informed by social identity theory, the author conducted ten semi-structured interviews with participants of a Professional Golf Management (PGM) University Program located in the American Southeast. Participants were found to form group associations with the PGM University Program and PGA of America early in the program of study, and garnered significant self-concept benefits as a result of their perceived group membership. The Playing Ability Test proved to be an influential point in the identity development phase as it provided tangible recognition of golf professional ability, while also leading to behavioral changes after successful completion. In addition, the identity of the participants was held in escrow by the PGM University Program and the PGA of America until completion of the symbiotic programs at which time participants could garner external affirmation of their group identity through PGA Class A certification. Theoretical and practical implications as well as future research directions are discussed.